The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10683-008-9211-7
|View full text |Cite
|
Sign up to set email alerts
|

Enjoy the silence: an experiment on truth-telling

Abstract: Experiment, Lying aversion, Social preferences, Strategic information transmission, Truth-telling, C72, C73, D83,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…The authors find that those subjects who punished lies with a higher probability are 5 those who exhibited higher rates of truth-telling in case they choose to send a message. Besides, similarly to our results, Sánchez-Pagés and Vorsatz (2009) show that the introduction of punishment does not increase the rate of truth-telling while senders switch to staying silent somewhat more often. At the same time, their setting had important differences from ours.…”
Section: Related Literaturesupporting
confidence: 91%
See 1 more Smart Citation
“…The authors find that those subjects who punished lies with a higher probability are 5 those who exhibited higher rates of truth-telling in case they choose to send a message. Besides, similarly to our results, Sánchez-Pagés and Vorsatz (2009) show that the introduction of punishment does not increase the rate of truth-telling while senders switch to staying silent somewhat more often. At the same time, their setting had important differences from ours.…”
Section: Related Literaturesupporting
confidence: 91%
“…These costs were shown to depend on the monetary consequences of a lie for both the sender and the receiver of the message (Gneezy 2005), senders' beliefs about the receiver (Sutter 2009, Beck et al 2013, form of communication (Lundquist et al 2009), or game experience (Gneezy et al 2013). Several papers so far considered the effect of the possibility of evasive communication (such as staying silent or using vague messages) on the informativeness of communication (see Sánchez-Pagés and Vorsatz 2009, Serra-Garcia et al 2011, Agranov and Schotter 2012. These studies show that many subjects use such communication patterns to circumvent both explicit lying and truth-telling.…”
Section: Related Literaturementioning
confidence: 99%
“…At the same time, for low levels of k lying is not very costly and the equilibrium messages m(t) are well above t. This implies in turn that the value of t for which m(t) = 10; is low. 19 Clearly, cuto¤ level t should be below t: Therefore, if k is small the separating segment should be short. When both b and k are su¢ ciently small the opposite requirements are incompatible and a LSHP does not exist.…”
Section: A2 Equilibria In the Presence Of Lying Costsmentioning
confidence: 99%
“…Other researchers have suggested that some individuals are simply lying-averse (Gneezy, 2005;Hurkens & Kartik, 2009), guiltaverse (Charness & Dufwenberg, 2006), sensitive to financial gains (Gibson et al, 2013;Ismayilov & Potters, 2013), justifiability (Erat, 2013;Erat & Gneezy, 2011), or motivated by a combination of factors such as financial gains, justifiability and a personal utility of honesty (Sakamoto et al, 2013). Another common finding from experimental literature is that investors rely more on the underwriters' reports than would be expected based on theoretical predictions (Kawagoe & Takizawa, 2008;Sanchez-Pages & Vorsatz, 2009). Deception is successful because investors appear receptive.…”
Section: Introductionmentioning
confidence: 99%